Clinical and Hematological Parameters of Captive Timor Deer (Rusa timorensis) under Physical Restraint - Virgilius Martin Kelake Kedang; Anita Esfandiari; Arief Purwo Mihardi; Robby Wienanto (HAYATI Journal of Biosciences, 2022)
Timor deer (Rusa timorensis) is native species in Indonesia that faces many threatening issues. Studies related to the health aspects of Timor deer are considered essential to provide some information related to deer health management in captivity. Deer handling procedures in captivity in Indonesia are commonly carried out with physical restraint. Physical restraint in animals is known to cause various changes in animals’ clinical and hematological values. This study aimed to determine the clinical and hematological parameters of Timor deer under physical restraint in captivity. This study used ten Timor deer that consisted of five stags and five hinds. The deer was positioned in a chute, then continued with the physical examination and blood sampling. Parameters observed in this study are clinical and hematological parameters. This study showed that clinical parameters of Timor deer under physical restraint have significant differences between sex groups, except for respiration rate parameters. Hematological parameters of physically restrained Timor deer did not show significant differences between sex groups, except for basophil parameters. This study concluded that physical restraint could affect the clinical and hematological parameters of Timor deer.